Exploring the knowledge and awareness of emulsifiers in food and non-food products among the community in Brunei Darussalam - Nurul Izzati Bustani; Aklimah Haji Mustapa (Journal of Halal Product and Research)
The demand for halal products in both food and non-food sectors is directly correlated with the growth of the Muslim population. Hence, it encompasses the prerequisite for utilising halal ingredients in producing the final product. Furthermore, there is a growing trend in the use of emulsifiers as a key ingredient in food and non-food products, which raises concerns about their prevalence, origin and impact on consumers' health. This research aims to investigate the level of knowledge and awareness among the community in Brunei Darussalam about the presence, source and health consequence of emulsifiers in food and non-food items. A quantitative approach was executed in this study. A questionnaire was developed and made available online for distribution to the general public of Brunei Darussalam via social media platforms. The data obtained from participants was recorded and analysed using SPSS Statistics version 23. Overall, the sample population was predominantly comprised of females, youths of aged 18-24 years old, students, individuals with a Bachelor's degree and Muslims. The results showed that the participants, particularly females and current students were significantly more knowledgeable of emulsifiers in food than non-food products. However, the overall knowledge degree of the ingredient among the participants was moderate. Furthermore, most responses exhibited a poor awareness level regarding the sources of emulsifiers and an uncertainty of their effects on human health. In conclusion, the findings of the present study will benefit consumers, particularly Muslims in Brunei Darussalam, to make informed decision on their purchasing of products as the information provided in the research enables them to distinguish between halal and non-halal products.